The relationship between organizational factors and employee performance / Muizzuddin Gazali - Gazali, Muizzuddin (Faculty of Business and Management, 2018)
The study aims to investigate the relationship between organizational factors and employee performance among employees in an organization. In this research study, the researcher decided to use working environment, leadership and compensation as the major factors of organizational towards employee performance. A total of 201 questionnaires had been distributed among the employees who work in SAJ Ranhill Sdn. Bhd. headquarters. Besides, researcher used descriptive and convenience sampling method in conducting this research. The researcher also used the Statistical Package in the Social Science Software (SPSS) version 20 to run all the data that have been collected. In general, the result of this research study has shown that all three independents variables which are the working environment, leadership and compensation have a strong relationship towards employee performance.